Upaya Perlindungan Anak oleh Lembaga Perlindungan Anak Indonesia Terhadap Korban Pelecehan Seksual - Majolica Ocarina Fae; R. Rahaditya (Universitas Ekasakti, 2024)
This research analyzes the efforts of child protection agencies in Indonesia to protect victims of sexual abuse. By employing qualitative analysis methods on relevant data, the main conclusion of this study is that child protection agencies face several constraints that limit their effectiveness in providing adequate protection to victims of sexual abuse. These constraints include limited resources, lack of coordination among agencies, low public awareness, limited access to protection services, and inconsistent law enforcement. Close collaboration between the government, civil society organizations, and all elements of society is needed to address these constraints and enhance child protection in Indonesia, particularly in the context of sexual abuse victims.